2019
DOI: 10.4236/ojce.2019.93013
|View full text |Cite
|
Sign up to set email alerts
|

Developing Suitable Proportions for the Production of Pineapple Leaf Fibers Reinforced Normal Strength Concrete

Abstract: The present work tried to develop suitable proportions for the production of Pineapple Leaf Fibers (PALF) reinforced Normal Strength Concrete (NSC), an experimental analysis with a mix ratio of 1:1.84:3.27 for cement: fine aggregates: coarse aggregates with constant water to cement ratio of 0.54. The total volume per mixing batch was calculated of 9 cubes + 9 cylinders + 3 beams in order to know the number of materials to be used in casting per batch, and the PALF percentage was taken based on cement weight wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In the case of the flexural strength of coconut-fiber-reinforced cementitious composites, most studies have reported increased flexural strength [243][244][245][246]272]. In a similar way, the majority of studies have reported enhancements in the flexural strength of jute- [247,248,251,273,274] (Figure 18d), hemp-[252-254] (Figure 18e), sisal- [4,256,275] (Figure 18f), pineapple- [83,258,260] (Figure 18g), sugarcane-bagasse- [4,263,275] (Figure 18h), and flax- [264][265][266][267] (Figure 18i) fiber-reinforced cementitious composites, compared to control specimens/composites. Overall, it may be concluded that, in comparison to compressive strength, the effect of fiber is more significant with respect to enhancements in the flexural strength of cementitious composites.…”
Section: Flexural Strengthmentioning
confidence: 81%
See 1 more Smart Citation
“…In the case of the flexural strength of coconut-fiber-reinforced cementitious composites, most studies have reported increased flexural strength [243][244][245][246]272]. In a similar way, the majority of studies have reported enhancements in the flexural strength of jute- [247,248,251,273,274] (Figure 18d), hemp-[252-254] (Figure 18e), sisal- [4,256,275] (Figure 18f), pineapple- [83,258,260] (Figure 18g), sugarcane-bagasse- [4,263,275] (Figure 18h), and flax- [264][265][266][267] (Figure 18i) fiber-reinforced cementitious composites, compared to control specimens/composites. Overall, it may be concluded that, in comparison to compressive strength, the effect of fiber is more significant with respect to enhancements in the flexural strength of cementitious composites.…”
Section: Flexural Strengthmentioning
confidence: 81%
“…The percentage differences in the compressive strength of pineapple, sugarcane bagasse, and flax fibers are shown in Figure 18g-i, respectively. In most of the reported studies, enhancement in the compressive strength was observed with respect to reference composites [83,[258][259][260][261][262][263][264][265][266]. However, Sawsen et al [267] reported reduced compressive strength for flax-fiber-reinforced concrete.…”
Section: Application Of Plant Fibers As Construction and Building Mat...mentioning
confidence: 99%
“…The substitution of M-sand with granite powder had a higher compressive strength compared to standard concrete. When granite powder is replaced by fine aggregate, there is an improvement in compressive strength [25]. As per IS: 516-1959, the compressive strength of SCC is checked.…”
Section: Fresh State Propertiesmentioning
confidence: 99%
“…B= weight after 12h of even dry 80°C using KOH Wt. C= weight after 12h of even dry 80°C using H 2 SO 4 The chemical properties (i.e., proportions of cellulose, hemicellulose and lignin) of the treated four fibers samples were determined based the procedure described by Direct method of cellulose, hemicelluloses and lignin [13] [14]. Alkali Treatment was done on the dry Pineapple leaf fibers using three different percentage of NaOH concentration, 3%, 5% and 7 % for 2 hours at 80°C to remove the unwanted soluble cellulose, hemi cellulose and lignin as shown in table 3.…”
Section: Chemical Properties Of Pineapple Leaf Fibersmentioning
confidence: 99%